2018
DOI: 10.1002/jsfa.9418
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pistacia vera adulteration by using laser induced breakdown spectroscopy

Abstract: BACKGROUND: Pistachio has high economic value because of its high consumption rate and consumer demand. Therefore, it has become an important target for adulteration. Green pea and spinach are the most frequently used foods for pistachio adulteration as a result of their kernel color. The present study aimed to detect pistachio adulteration with green pea and spinach samples using laser induced breakdown spectroscopy (LIBS) combined with chemometric methods. RESULTS:In the first step of the study, principal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Green pea adulteration in the economically valuable pistachio nuts was recently addressed with two reports that describe the utilization of spectroscopic approaches . Unlike the limited number of existing studies related to the issue, the present work belongs to the discipline of food genomics and describes ‘genetic testing’ adapted to pistachio authenticity analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Green pea adulteration in the economically valuable pistachio nuts was recently addressed with two reports that describe the utilization of spectroscopic approaches . Unlike the limited number of existing studies related to the issue, the present work belongs to the discipline of food genomics and describes ‘genetic testing’ adapted to pistachio authenticity analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The issue of the detection of adulteration in pistachio nuts was addressed only recently by two reports that describe spectroscopic methods. Raman hyperspectral imaging and laser‐induced breakdown spectroscopy were coupled with chemometric analyses to predict green pea adulteration in pistachio nuts in both studies.…”
Section: Introductionmentioning
confidence: 99%
“…Observation of ceramides with a modified long chain base and with specific fatty acids may increase the variety of chemical indicators that can be employed to confirm the presence of specific high-value nuts, such as pistachios and almonds, in food preparations, and to highlight contamination or adulteration with extraneous materials [2,24,25]. Several techniques are currently used for this task, including direct Near-Infra-Red [26] and Raman [27] spectroscopy, mineral element pattern [28], and chemometric evaluation of untargeted LC-HRMS analysis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pistachio nuts are frequently supplied by the confectionary sector and by Turkish dessert factories in a ground form. Previous studies have reported that green peas, spinach, and peanuts with food dyes have been used as adulterants in the case of ground pistachio nuts 8,9 . A market search showed that a markedly cheaper product referred to as ‘decorative peanut’ – a mixture of peanut flour, sugar, starch, and green food dye – is used in confectionery products instead of authentic pistachio nuts.…”
Section: Introductionmentioning
confidence: 99%
“…In another previous study, Sezer et al . (2019) successfully detected green pea and spinach adulteration in pistachio nuts using laser‐induced breakdown spectroscopy 8 …”
Section: Introductionmentioning
confidence: 99%